Antecedents for actual usage intentions of open access journals in agricultural research institutions in Tanzania - Zubairi Massoro, Zainabu; Othman, Roslina (University of Idaho Library, 2017)
The purpose of this paper is to examine antecedents that predict researchers’ usage intention of Open Access Journals (OAJs) in Tanzania, with a specific focus on the Agricultural Research Institutes (ARIs). Specifically, the study investigates major predictors of usage intentions of OAJs. Data were collected from pilot study. A total of 60 (85.71%) usable questionnaires out of 70 were returned. The study utilized the Theory of Reasoned Action (TRA). The results show that attitude, content respectability and predatory publishers have insignificant effect on usage intention, while subjective norms and intention shows statistically significant effect on OAJs usage behavior. The study findings are useful to OAJs publishers and ARIs management staff to identify important factors and safeguard policies on Open Access publishing and strategies to encourage long-term usage of OAJs for future studies and lifelong learning. By using TRA in the context of actual usage intentions and the integration of an additional construct “content respectability and predatory publisher”, the extended TRA model fits very well in the OAJs in Tanzania, in particular where such studies are scant. The findings can be used in other institutions with similar conditions in investigating OAJs usage intentions.